Modelo estatístico para cálculo do Fator de Segurança Global de Estaqueamentos - Joia, Luiz Antonio (1981)
The quality control of piled foundations becomes necessary in very important constructions. However, a deterministic analysis is impossible because of the great number of piles in the foundation. It's necessary to create a statistical model that using a sample, especially choosen for this, simulates conveniently the statistical universe. This thesis uses Weibull 's theory of probability applied in piles and the Monte-Carlo Simulation combined with the Central Limit Theorem of Statistics, for calculation of the global safety factor. It's showed a practical example and the computer programs used for the simulation. This method is usable in rigid pile-head slabs, and in foundations set on rocks.